Economic impact of early intervention in people at high risk of psychosis. - Valmaggia, L; McCrone, P; Knapp, M; Woolley, J; Broome, MR; Tabraham, P; Johns, L; Prescott, C; Bramon, E; Lappin, J; Power, P; McGuire, P (2009)
BACKGROUND: Despite the increasing development of early intervention services for psychosis, little is known about their cost-effectiveness. We assessed the cost-effectiveness of Outreach and Support in South London (OASIS), a service for people with an at-risk mental state (ARMS) for psychosis. METHOD: The costs of OASIS compared to care as usual (CAU) were entered in a decision model and examined for 12- and 24-month periods, using the duration of untreated psychosis (DUP) and rate of transition to psychosis as key parameters. The costs were calculated on the basis of services used following referral and the impact on employment. Sensitivity analysis was used to test the robustness of all the assumptions made in the model. RESULTS: Over the initial 12 months from presentation, the costs of the OASIS intervention were pound1872 higher than CAU. However, after 24 months they were pound961 less than CAU. CONCLUSIONS: This model suggests that services that permit early detection of people at high risk of psychosis may be cost saving.